2020
DOI: 10.1111/vec.13020
|View full text |Cite
|
Sign up to set email alerts
|

In vitro iatrogenic hemolysis of canine packed red blood cells during various rapid transfusion techniques

Abstract: Objective To evaluate which rapid blood administration technique causes the least iatrogenic hemolysis in canine packed red blood cells (pRBCs) as determined by plasma free hemoglobin (fHb) and percent hemolysis (% hemolysis). Design Prospective in vitro randomized study. Setting Private referral center. Animals None. Interventions Thirteen units of canine pRBCs were divided equally into 5 aliquots, resulting in 65 trials. The aliquots of each unit were subjected to the following administration techniques: gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Five samples on the day of collection and three samples at D35 had a haemolysis percentage that decreased between pre-and post-filter passage analysis. Similar results have been found in humans 25 and dogs, 43 and the reasons for this are unclear. Proposed mechanisms include the settling of blood during the transfusion and/or partial filter occlusion, leading to inconsistencies in HCT/PCV and plasma Hb results.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Five samples on the day of collection and three samples at D35 had a haemolysis percentage that decreased between pre-and post-filter passage analysis. Similar results have been found in humans 25 and dogs, 43 and the reasons for this are unclear. Proposed mechanisms include the settling of blood during the transfusion and/or partial filter occlusion, leading to inconsistencies in HCT/PCV and plasma Hb results.…”
Section: Discussionsupporting
confidence: 75%
“…A recent canine study found no significant increase in haemolysis percentage in PRBCs stored for <14 days after passage through an 18 µm filter at maximal manual infusion rates. 43 The clinical significance of transfusing blood with >1% haemolysis has not been established in cats. Free haemoglobin induces oxidative stress, with potentially detrimental effects to renal, myocardial and vascular systems.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies in dogs (LOE 3, good) have looked at red blood cell viability using different infusion methods 161–164 . Only one (LOE 3, good) looked at in vivo red blood cell survival.…”
Section: Domain 1: Prevention Strategiesmentioning
confidence: 99%
“…160,165 A recent study in dogs also showed minimal hemolysis using the same piston pump. 161 Further studies looking at red blood cell in vivo survival of different age products with different pumps are needed. In addition, including administration method in future transfusion studies in dogs looking at improvement in PCV after transfusion would be useful.…”
Section: Agreement: 13/13 Evidence Summarymentioning
confidence: 99%
“…Research performed on blood being given to dogs identified that administration via a pump or syringe driver resulted in a decreased lifespan of transfused cells compared with administration under gravity (McDevitt and others 2011), and a reduced improvement in packed cell volume after transfusion (Weltman and others 2014). However, recent work evaluating the effect of rapid infusion of canine packed RBCs did not identify increased haemolysis associated with administration through a syringe driver or pump (Weeks and others 2021). There is no evidence that administration using a syringe driver through a microaggregate filter decreases RBC lifespan in cats (Heikes and Ruaux 2014).…”
Section: Methods Of Administrationmentioning
confidence: 99%